Publication trends of leadership excellence: a bibliometric review using VOS viewer / Khairul Hafezad Abdullah - Abdullah, Khairul Hafezad (Universiti Teknologi MARA, 2021)
Leadership research has long attracted interest among researchers. Analyzing the evolution and development of this scientific domain is therefore essential. This study discusses the bibliometric review of scholarly research performed in leadership excellence in recent years. The study uses the Scopus database and a wide variety of bibliometric indicators such as publication trends, citations, and authors' keywords. Graphical visualization of bibliometric using VOS viewer software is also presented. Results showed that the number of studies covering this topic has fluctuated and is still minimal, with fewer than ten publications per year over four decades. It could also be interpreted that leadership excellence research is broad by evaluating publications and research areas. The bibliometric review conducted provides a comprehensive and in-depth view of leadership excellence research that may be of interest to researchers who are keen to improve or discover new knowledge in this area.